2020
DOI: 10.1149/2162-8777/ab9fe9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modelling Investigation of Re-Adhesion Mechanism of Detached Nanoparticles to Wafer Surface in Spin Rinse Process

Abstract: Adhesive particles on polished wafers are detached by e.g. scrubbing, and removed by liquid flow from the wafer. However, the relationship between the characteristic of liquid flow and the removal of detached particles has not yet been examined in detail. Therefore, the re-adhesion of detached particles to wafer surfaces in liquid flow on rotating wafers was experimentally investigated. The number of residue particles on a wafer was counted using a defect inspection tool after de-ionized water (DIW) rinse for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…As noted above, a previous study revealed that the number of particles readhering to the wafer depended on the Sherwood number, which is a dimensionless number used in mass transfer operations. 12 Here, it was found that the readhesion particles could not be removed from the wafer or the vicinity of the wafer when the liquid type in step 1 was DIW. 12 While it was considered that the number of readhering particles would vary depending on the zeta potential, the effect of the interaction between the particle and the wafer in relation to the zeta potential could not be considered in the previous model.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…As noted above, a previous study revealed that the number of particles readhering to the wafer depended on the Sherwood number, which is a dimensionless number used in mass transfer operations. 12 Here, it was found that the readhesion particles could not be removed from the wafer or the vicinity of the wafer when the liquid type in step 1 was DIW. 12 While it was considered that the number of readhering particles would vary depending on the zeta potential, the effect of the interaction between the particle and the wafer in relation to the zeta potential could not be considered in the previous model.…”
Section: Discussionmentioning
confidence: 91%
“…12 Here, it was found that the readhesion particles could not be removed from the wafer or the vicinity of the wafer when the liquid type in step 1 was DIW. 12 While it was considered that the number of readhering particles would vary depending on the zeta potential, the effect of the interaction between the particle and the wafer in relation to the zeta potential could not be considered in the previous model. 12 Therefore, with reference to the DLVO theory and the theory of Brownian motion near the wall, the effect of the zeta potential was incorporated into the model.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Thin-liquid-film flows are frequently encountered in various industrial applications such as steam turbines for power generation (Baumann, 1921;Kawagishi et al, 2011), chemical reaction devices such as falling film evaporators (Li et al, 2016), and single-wafer cleaning in semiconductor-device manufacturing (Handa et al, 2020). Moreover, the film thickness is directly related to the safety, efficiency, and yield improvement of these devices.…”
Section: Introductionmentioning
confidence: 99%